HUBUNGAN ANTARA UKURAN PERUSAHAAN DAN PROFITABILITAS DENGAN PENGUNGKAPAN CSR PADA PERUSAHAAN YANG TERDAFTAR DI DAFTAR EFEK SYARIAH 2013 (THE CORRELATION BETWEEN FIRM SIZE AND PROFITABILITY WITH CSR DISCLOSURE OF COMPANIES LISTED OF SHARIA SECURITIES (DAFT - Arum Ariftyarini; Ratna Anggraini ZR; Erika Takidah (Jurnal Ilmiah Econosains, 2014)
ABSTRACTThe Correlation Between Firm Size and Profitability With CSR Disclosure of Companies Listed of Sharia Securities (Daftar Efek Syariah (DES)) in 2013. Faculty of Economics. State University of Jakarta, 2014. This study aims to examine the relationship caused by firm size and profitability with CSR disclosure of companies listed of sharia securities (daftar efek syariah) in 2013. Data were obtained from the Bursa Efek Indonesia (BEI) in 2013. The sampling technique was conducted by random sampling. The attainable population in this research were all mine and manufacture companies listed of Sharia Securities (Daftar Efek Syariah) in two periode of 2013 is 69 companies. The sample used by the table Isaac and Michael is 58 companies. The simple linear regression and resulted Å¶ = -1,351 + 0,057SIZE + 0,315PROFIT. Correlation between the firm size of the CSR disclosure is significantly possitive. But between the profitability and the CSR disclosure there is not found significantly relationship. In silmutan, the correlation between firm size and profitability with the CSR disclosure is significantly positively correlated. Normality test results were calculated with SPSS shows that all the variables above 0.05, inicated normally distributed. In partial test, significance t_hitung Firm size is 6,015 with significance 0,000 so, it indicated possitive significantly related between them. But Profitability just 1,928 with the significance 0,059 and there is no significantly related.Keywords: Firm Size, Profitability, CSR Disclosure.*